2013
DOI: 10.19030/iber.v12i3.7672
|View full text |Cite
|
Sign up to set email alerts
|

Present-Day Dillemas And Challenges Of The South African Tertiary System

Abstract: ABSTRACT

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 22 publications
0
22
0
Order By: Relevance
“…Confirming the notion that cultural change does not necessarily happen because of political change, Mouton, Louw and Strydom (2013) observed that while mergers and restructuring in higher education accentuated quality and raised academic levelling, but still the process included resistance. The introduction and the implementation of democratic policies cannot lead to the complete eradication of inequality in education on their own.…”
Section: Conceptual-and Theoretical Frameworkmentioning
confidence: 70%
“…Confirming the notion that cultural change does not necessarily happen because of political change, Mouton, Louw and Strydom (2013) observed that while mergers and restructuring in higher education accentuated quality and raised academic levelling, but still the process included resistance. The introduction and the implementation of democratic policies cannot lead to the complete eradication of inequality in education on their own.…”
Section: Conceptual-and Theoretical Frameworkmentioning
confidence: 70%
“…Ives and Rowley (2007:546) report that when the supervisor "was not sufficiently close to the subject area", he/she was unable to advise students adequately and that he/she "can go off on a tangent". This brings into consideration whether supervision outside the field of expertise reaches its full potential, firstly, by providing applied research to serve industries (Kraak (2006) in McKenna and Powell, 2009) and, secondly, the supervisors' personal mastery and progress towards publications and possible promotion (Ntshoe and de Villiers (2008) in Mouton, Louw and Strydom, 2013).…”
Section: Implications Of Supervisor Survey Resultsmentioning
confidence: 99%
“…Language and the mastery of English as a medium of instruction is a significant barrier for many black students for whom English is a second or third language and (Mouton, Louw and Strydom 2013).…”
Section: Languagementioning
confidence: 99%